General and specific combining ability effects for yield and its components in maize diallel crosses - Hager, Mohamed A.; El-Hashash, E. F.; Ali, M.A.M. (2015)
A half diallel cross comprising seven inbred lines were studied for six traits to determine combining ability in parents and their F 1 crosses. This study have focused attention on procedural aspects for exploiting combining ability in order to predict hybrid performance and identifying F 1 's to be utilized in maize breeding programs. The mean squares of genotypes were highly significant for all studied traits duri.ng the two seasons. Mean performance of most single crosses were higher than the parents for all studied traits during the two seasons. The hybrid L155 x Ll 76 was the best mean performance for most studied traits. Based on the general combining ability (GCA) effects the parents L155 and L206 were identified as good combiners for most yield and yield component traits in diallel analysis during 2011 and 2012 seasons. These parents can be used in pedigree breeding for incorporation of desired traits. The SCA effects for hybrid combinations L155 x L207 for ear length, L2U x L232 for number of kernels/row, Ll55 x L172 for number of rows/ear, L207 x L212 for number Of kernels/ear and L155 x L176 for 100-kemel weight and grain weight/ plant were found to be the best specific combinations. Grain yield/plant showed a highly significant positive association with other studied traits i.e., ear length, number of kernels/row, number of rows/ear, number of kernels/ear, 100- kernel weight and grain weight/plant during the two seasons, hereby improving grain yield in com is possible through selection for the previous traits.
Includes references.
Summary in Arabic.
1
Keywords: Corn -- Hybrids -- Physiology and morphology; Corn -- Yields